Recent advances in the enzymatic synthesis of sugar-nucleotides using nucleotidylyltransferases and glycosyltransferases - Ahmadipour, Sanaz; Beswick, Laura; Miller, Gavin J. (Carbohydrate research, 2018)
Sugar-nucleotides are imperative to carbohydrate metabolism and glycoconjugate biosynthesis. Enzymatic methods to access these key materials offer a powerful alternative to traditional chemical synthesis routes. Herein we review recent advances in the enzymatic pyrophosphorylation of glycosyl 1-phosphates for the provision of both native and modified sugar-nucleotides. [Display omitted]